Proyecto para el diseño de un sistema híbrido eólico-fotovoltaico para el complejo deportivo “Cancha Sho” en la ciudadela Bellavista de la ciudad de Guayaquil. - Quinzo Lucas, Luis Fernando (2019)
The present work is carried out in order to carry out an electrical design and study of renewable sources by means of solar and wind energy or also known as "hybrid", the study that has been carried out by means of investigative methods such as documented, descriptive texts and explanatory statements indicating the reasons for the greenhouse effect due to petroleum products and their toxic gases, as well as the effort to reduce these problems with the productivity indexes that exist worldwide with photovoltaic and wind energy. These systems are therefore an inexhaustible source of energy so this work presents studies already conducted by other authors of solar energy levels that can deliver the sun as well as studies of wind speeds of all regions of Ecuador. It will also describe how to obtain the energy demands that the hybrid system requires for the good behavior of the solar panels and not be affected by red dots caused by its high temperature, in addition to the care that must be taken when managing certain bank tensions. of batteries as their proper protections that must be incorporated into the system, as well as how to properly size the regulators, inverters and batteries with steps that must be followed to perform a safe and reliable installation.